BILINGUALS’ LINGUISTIC REPERTOIRE AND FOREIGN LANGUAGE INSTRUCTION: WHAT DO TEACHERS SAY ABOUT TEACHING EFL THROUGH TRANSLANGUAGING? - Gede Eka Putrawan; Tuntun Sinaga (JOURNAL OF LANGUAGE, 2022)
In recent decades, translanguaging has made rapid progress in the field of language instruction. The term "translanguaging" implies that bilinguals have a single linguistic repertoire from which they strategically select linguistic features for effective communication. The current method of language education, which takes a monolingual approach, faces a challenge from the phenomenon known as translanguaging. Therefore, this study aims to describe the perspectives of Indonesian EFL teachers on translanguaging-based EFL instruction for students from a variety of linguistic backgrounds. This is a qualitative study employing interviews to collect data, with eight EFL teachers serving as participants. A content analysis was used to analyze the collected data. This study suggests that EFL teachers have divergent perspectives on translanguaging in EFL classrooms. However, those with negative attitudes toward translanguaging recognize the importance of this pedagogical approach and continue to use L1 in their EFL classrooms, indicating that they still believe in monolingual pedagogy even though they do not fully apply it. Finally, the study's implications and limitations are discussed.